2012
DOI: 10.3758/s13428-012-0246-5
|View full text |Cite
|
Sign up to set email alerts
|

Motion-induced blindness measured objectively

Abstract: During central fixation, a moving pattern of nontargets induces repeated temporary blindness to even salient peripheral targets: motion-induced blindness (MIB). Hitherto, behavioral measures of MIB have relied on subjective judgments. Here, we offer an objective alternative that builds on earlier findings regarding the effects of MIB on the detectability of physical target offsets. We propose a small modification of regular MIB displays: Following a variable duration (lead time), one of the targets is physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Given that a processing tendency should be more flexible than a processing disability, with a deadline experiment (an experiment in which subjects are forced to respond before a variable deadline; e.g., Kramer et al, 2013) these two accounts can be pitted against each other. At a long deadline, some may have a large Ebbinghaus illusion and some may have a small one.…”
Section: Discussionmentioning
confidence: 99%
“…Given that a processing tendency should be more flexible than a processing disability, with a deadline experiment (an experiment in which subjects are forced to respond before a variable deadline; e.g., Kramer et al, 2013) these two accounts can be pitted against each other. At a long deadline, some may have a large Ebbinghaus illusion and some may have a small one.…”
Section: Discussionmentioning
confidence: 99%
“…Those results indicate that the offset does not always trigger consciousness; it should be given at the right time just before a (spontaneous) emergence of a conscious percept. In the previous studies using MIB and Troxler fading (Klotz & Ansorge, 2007;Kramer et al, 2013;Lleras & Moore, 2006;Montaser-Kouhsari et al, 2004), an offset was introduced at a random time in an "invisible" period during which a strength of perceptual suppression fluctuated over time. If the offset had been constantly provided at the end of the invisible period (when the perceptual suppression was weak and the disinhibition was in progress), they might have observed the offsettriggered consciousness as the present study.…”
Section: 3mentioning
confidence: 99%
“…Time dependency of the offset-triggered conscious perception While we used CFS (inter-ocular suppression) to create a unique situation in which an invisible stimulus physically disappeared from a screen, several studies have tested similar situations using other psychophysical techniques to render a stimulus invisible, such as motion-induced blindness (MIB) (Klotz & Ansorge, 2007;Kramer, Massaccesi, Semenzato, Cecchetto, & Bressan, 2013;Montaser-Kouhsari, Moradi, Zandvakili, & Esteky, 2004) and Troxler fading (Lleras & Moore, 2006). Those studies, however, consistently reported no evidence for the offset-triggered conscious perception; subjects failed to detect an offset of an invisible stimulus because it induced no perceptual change.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Different subliminal approaches reveal that suppression hardly affects superficial level of visual processing, such as spatial frequency, motion-direction, color, and orienting (Long and Toppino, 2004; Breitmeyer and Ögmen, 2006; Breitmeyer, 2007; Whitney and Levi, 2011; Yang and Blake, 2012; Kramer et al, 2013). A more complex picture has emerged concerning deeper levels of subliminal processing (van Gaal and Lamme, 2012).…”
Section: Part II – Contemporary Approaches To the Study Of The Cognitmentioning
confidence: 99%